Novel Therapeutic Targets for Hypoxia-Related Cardiovascular Diseases: The Role of HIF-1 - Liu, Minxuan; Galli, Gina; Wang, Yilin; Fan, Qiru; Wang, Zhenzhong; Wang, Xin; Xiao, Wei (Frontiers in Physiology, 2020)
Insufficient oxygen availability (hypoxia) is a precursor to numerous cardiovascular diseases, including atherosclerosis, pulmonary hypertension and heart failure. The main site of hypoxic injury in the human body is the mitochondria, where oxygen acts as the final electron acceptor in the process of oxidative phosphorylation. Hypoxia inducible factor (HIF) is activated in hypoxic conditions and acts as an important modulator of diverse target genes in the human body. The downstream genes of HIF include vital modulators of cardiovascular-related signaling pathways. Therefore, it is hypothesized that HIF represents a potential therapeutic target for the treatment and prevention of cardiovascular diseases. In this short review, we introduce the pathophysiology of hypoxic injury in cardiovascular disease, and we conclude from convincing evidence that HIF can modulate relevant cardioprotective signaling pathways.